2019
DOI: 10.1016/j.jsps.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Practices, awareness and attitudes toward self-medication of analgesics among health sciences students in Riyadh, Saudi Arabia

Abstract: BackgroundSelf-medication is a common practice among health sciences students in Saudi Arabia. It is known that inappropriate selfmedication may harm individuals due to increasing the risk of drug misuse or delaying a hospital visit by masking some symptoms. Thus, the aim of our study is to investigate and assess practices, awareness and attitudes toward analgesics self-medication among health science students in Riyadh, Saudi Arabia.MethodsThis is a cross-sectional study in a form of electronic survey that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 15 publications
(38 reference statements)
9
31
1
2
Order By: Relevance
“…27,28 In the present study, the most common reasons for the utilization of SM with OTC medications were; to save time 77.4%, Quick relief 62.4%, and for treatment of minor ailments 49.6%. Similar findings were reported by a study conducted in Saudi Arabia 29 and Pakistan 30 in which in the former case, a desire to avoid long waiting time to see physician 39% followed by a need to not burden the physician for minor illness 26% were the commonest reasons for SM, while in the latter one, mild nature of the disease 34.3% followed by the easy availability of the drugs (30.1%) were the most common reasons for SM practices. This is evident because the study participants being medicine and health science students make them familiar with diseases and their treatment (medications) which will in turn make them opt to treat themselves without consulting regular physicians.…”
Section: Discussionsupporting
confidence: 83%
“…27,28 In the present study, the most common reasons for the utilization of SM with OTC medications were; to save time 77.4%, Quick relief 62.4%, and for treatment of minor ailments 49.6%. Similar findings were reported by a study conducted in Saudi Arabia 29 and Pakistan 30 in which in the former case, a desire to avoid long waiting time to see physician 39% followed by a need to not burden the physician for minor illness 26% were the commonest reasons for SM, while in the latter one, mild nature of the disease 34.3% followed by the easy availability of the drugs (30.1%) were the most common reasons for SM practices. This is evident because the study participants being medicine and health science students make them familiar with diseases and their treatment (medications) which will in turn make them opt to treat themselves without consulting regular physicians.…”
Section: Discussionsupporting
confidence: 83%
“…In present study, the prevalence of self medication with analgesics was found to be 83.3% while in studies done by Badiger et al, Shivamurthy et al, Al Essa et al, found prevalence of analgesic self medication to be 92%, 63.6% and 73.2% respectively. 4,8,9 Present study thus supports earlier studies with similar results signifying increasing self medication practice among medical students.…”
Section: Discussionsupporting
confidence: 91%
“…In present study, self medication with analgesics was used for headache (59.7%) and Nonsteroidal antiinflammatory drugs (NSAIDs) (90%) were the commonly used drugs which is similar to studies done by Shivamurthy et al, Al Essa et al, where headache (68.2% and 92% respectively) was the most common indication and NSAID paracetamol (47%, 96.5%) was most commonly used analgesic. 8,9 This practice of self medication with analgesics for minor illness is common as they believed that no other medical intervention is required. This trend of analgesic self-use could mask the actual diagnosis of the underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence of self medication with analgesics was found to be 79 % and 72% in group I and group II respectively while in studies done by Badiger et al, Shivamurthy et al, Al Essa et al, prevalence of self medication with analgesic was found to be 92% , 63.6% and 73.2% respectively. [11][12][13] Our study thus supports earlier studies with similar results signifying increasing practice of self medication among medical students.…”
Section: Discussionsupporting
confidence: 91%
“…The commonest condition for self medication with analgesics was headache (75.8% in group I and 59.7% in group II, p=0.0172) and NSAIDs ( 80.6% in group I and 90% in group II, p=0.0780) were the commonly used drugs which is similar to studies done by Shivamurthy et al, Al Essa et al, where headache (68.2% and 92%) was the most common indication and NSAID (47%, 96.5%) was most commonly used analgesic respectively. 12,13 This practice of self medication with analgesics for minor illness is common among medical students.…”
Section: Discussionmentioning
confidence: 99%